Preventing litigation : an early warning system to get big value out of big data - Brestoff, Nelson E., (Business law collection., 2015)
The legal profession must change. Today, attorneys don't think of ways to do less litigation. When the damage is done, they examine the wreck at the bottom of the cliff and offer to represent one side or the other. Preventing Litigation, for the first time, explains how to build an early warning system to identify the risk of litigation before the damage is done, and proves that there is big value in less litigation. This book puts everyone where they should be: at the top of the cliff. The authors are subject matter experts, one in litigation, the other in computer science, and each coauthor has more than four decades of training and experience in their respective fields. Together, they present a way forward to a transformative revolution for the slow-moving world of law for the benefit of the fast-paced environment of the business world.